iLife '11 made simple - Durdik, Glen (Berkeley, CA Apress, 2011)
Are you new to the Macintosh experience and iLife? Or are you someone who wants to know the ins and outs of Apple?s powerful media creation tools? Either way, you have come to right place. iLife '11 Made Simple will guide you through the iLife apps and help you become a power user in no time. iLife '11 Made Simple lets you be creative with iPhoto, iDVD, iMovie, iWeb, and GarageBand?from the initial welcome screen to the last menu item. Even though iTunes is not part of the retail package, it is an important part of the creation or sharing process and is covered in this book as well. You'll also learn how iLife apps work on iOS devices as well as how they work with iCloud.  So, if you just want to learn how to create a basic movie, song or website, iLife '11 Made Simple is perfect for you. Want to become a media mogul in any of the covered applications? After reading this manual, you'll be swept into the creative process and be well on your way to creating or enhancing your next iLife masterpiece! You already own the most powerful and easy-to-use computer in the known universe. With this guide in hand, you'll see how Apple applies its magic to incredible software packages as we
Electronic reproduction.
Keywords: iLife; Interactive multimedia; Macintosh (Computer)